Orf Virus (ORFV) Infection in the Mouth of Lambs and Kids Detected by Molecular Investigation - Kaya, Güler Berat; Kale, Mehmet (Acta Scientiae Veterinariae, 2025)
Background: Contagious Ecthyma infections caused by Parapoxvirus ovis are an important viral disease of sheep and goats. It is an infection with high mortality that especially affects young animals. The majority of orf virus (ORFV) infections are diagnosed using molecular diagnostic techniques (multiplex, conventional, real-time PCR). Scab samples were collected from lesions developed due to ORFV in the mouths of 50 lambs and 50 kids that were not vaccinated against ecthyma disease from public pens in Burdur-Center and surrounding areas. The main objective of the study was to investigate the ORFV genome in the samples using the conventional PCR method with 25 different types of primers. Materials, Methods & Results: Scab samples were collected from lesions defined because of ecthyma disease in the mouth (lips, gums) of 50 lambs and 50 kids aged ≤ 1 month to 3 months in various public pens. In the study, high viral genome positivity was determined in local breed lambs (Sakiz sheep; 40%) and kids (Kil goat; 36%). ORFV genome presence was detected more positivity in female lambs (60%) and kids (46%) than in males. ORFV genome presence was detected more positivity in lambs (36%) and kids (40%) aged ≤ 1 month, than in those in the 2- and 3-month age group. In this study, with use of PCR applications, ORFV was predominantly detected in the Burdur region; GIF/IL2, PPP1-PPP4, Orf1-Orf2, VIR1 VIR2, vIL-10-3 vIL-10-4, B2L and Alpha tubulin primers was detected. No positivity was obtained in PCR analysis using PPV JGR, ORFV 011-B and ORFV 109 primers. In our study, it was found that the groups with the most binary ORFV primers were found at the highest rate in the tissues. Discussion: Contagious Ecthyma infection caused by Parapoxvirus ovis is an important viral disease of sheep and goats. It is an infection with high mortality that especially affects young animals. The infection primarily affects animals under one year of age, and it also affects animals three to four months after birth. Therefore, it is a disease that causes both economic and productivity loss. Due to factors like weight loss and weakened immunity brought on by limited amounts of breast milk and feed intake because the lesions are in the mouth, ecthyma has a more severe effect on lambs and kids than it does on adults. The susceptibility of animals to secondary infections may increase. Young animals die at a higher rate as a result. The mortality of the majority of the offspring in that herd at that time and the development of productivity losses are indicators of the spread of ORFV in small cattle farms over time. Many classical diagnosis methods are used in the disease. Molecular diagnostic methods are mainly used in ORFV infections because they are sensitive, rapid and low-cost. One of these is the PCR application, which is used worldwide and in Turkey and yields findings more quickly than other techniques. In the research, the presence of viral genome was investigated by PCR using 25 different types of primers in the oral lesions of lambs and kids. In this study, the presence of ORFV in lesions occurring in the mouth area of lambs and kids was investigated molecularly. In the current study, ORFV was detected in most of the 7 primers, and the groups with the most binary ORFV primers were found at the highest rates in the tissues. As a result, the presence of ORFV was detected molecularly in the lesions occurring in the mouth area of lambs and kids of different breeds. Keywords: ecthyma, kid, lamb, PCR, Orf virus.